2021
DOI: 10.1016/j.jand.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes and Severity of Irritable Bowel Syndrome Are Not Related to Patients’ Self-Reported Dietary Triggers: Results From an Online Survey in Dutch Adults

Abstract: Background Diet plays an important role in symptom management of irritable bowel syndrome (IBS). However, current diet therapies are not optimal nor successful for everyone. Objective To investigate whether subgroups based on IBS subtypes or severity identify different self-reported dietary triggers, and whether these are associated with severity and psychological factors. Design Online cross-sectional survey Participants Patients with IBS (n ¼ 1601) who fulfilled the Rome IV criteria or had an IBS diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Associations between fatty meal consumption and IBS symptoms have also been identified in a number of studies. In fact, in many IBS patients, the symptoms were triggered after the consumption of greasy or fried food [ 45 , 46 ]. Dietary fat is also linked to an increased risk for developing IBD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between fatty meal consumption and IBS symptoms have also been identified in a number of studies. In fact, in many IBS patients, the symptoms were triggered after the consumption of greasy or fried food [ 45 , 46 ]. Dietary fat is also linked to an increased risk for developing IBD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of self-reported wheat sensitivity has been reported at approximately 10% globally [12]. Wheat appears to be a key trigger for symptoms in patients with IBS, reported at between 23 and 49% of individuals [5,[13][14][15].…”
Section: Gluten-free Dietmentioning
confidence: 99%
“…In addition, there seems to be a significant overlap between NCG/WS, IBS, and functional dyspepsia ( 37 , 38 ). It has previously been demonstrated that a large proportion of individuals with IBS have sensitivity to wheat, reported at between 23% and 49% ( 1 , 39 , 40 ). A key distinguishing feature between both IBS and NCGW/S is that individuals with NCG/WS tend to identify gluten as a trigger and self-report symptoms after the consumption of gluten.…”
Section: Nonceliac Gluten/wheat Sensitivitymentioning
confidence: 99%